CLIL and elitism: myth or reality?. Issue 1 (2nd January 2020) - Pérez Cañado, María Luisa
ABSTRACT: This article aims to shed light on the question of elitism in CLIL by exploring empirical evidence taken from a large-scale longitudinal investigation based in Spain. To this end, it reports on a quantitative study into the effects of CLIL programmes on the English language attainment of primary and secondary education students in monolingual contexts. The study uses a sample of 2024 students from twelve monolingual provinces in Spain; has guaranteed the homogeneity of bilingual and non-bilingual groups; and has factored in several intervening variables. It approaches the topic from a three-pronged perspective: by determining whether the most motivated, intelligent, and linguistically proficient students are in fact found in CLIL groups; by analysing the possible differential effect of socio-economic variables on L2 attainment; and by examining whether CLIL has the potential to work even in disadvantaged contexts. The results suggest that, while certain variables impact on language education in both CLIL and non-CLIL settings, others do not have such a substantial effect in CLIL scenarios as in non-bilingual settings. Thus the broader take-away is that commonly harboured beliefs vis-à-vis the elitism of bilingual programmes need to be re-examined and a possible future research agenda is suggested to continue advancing in this area.